Integrating Mathematical Modeling of Real-Life Problems: A Contextualized Approach to Developing Instructional Material in Basic Calculus - Pelemeniano, Airish P.; Siega, Marvin H. (International Journal of Membrane Science and Technology, 2023)
This study focuses on the creation of contextualized educational materials for senior high school basic calculus that integrates mathematical modeling with real-life problems. The research follows the ADDIE model employing only three stages: analysis, design, and development (ADD). In the analysis phase, the researcher determines the level of modeling competency, self-efficacy, and appreciation of the learners using the Assessment of the Modeling Skills (RAMS), Indices for Mathematical Modeling Self-Efficacy Scale (IMMSES), and the Indices for the Level of Appreciation of Mathematical Modeling (ILAMM) respectively. The results from the previous phase were considered in designing and developing contextualized instructional material that aligned with the concepts of didactical situations and mathematical modeling. Quantitative data analysis includes descriptive statistics to determine the level of modeling competency, self-efficacy, and appreciation of the learners and the assessment of the teachers on the mathematical modeling activities. This study also reveals that the learner’s lack of prior knowledge in algebra and trigonometry contributed to the difficulty in solving real-life problems in Basic Calculus. Moreover, teaching materials are limited only on problem-solving and formative assessment. With this, the researchers designed and developed instructional materials that incorporate a variety of resources, including problem scenarios, data sets, visualizations, and technology tools, to facilitate students’ exploration and analysis of the modeled problems. Ultimately, it aims to enhance students’ understanding and engagement by providing them with meaningful and practical applications of the subject matter.